Effect of Games towards Children's Mathematics Performance - Connie Cassy Ompok; Ling Mei Teng; Jaini Sapirai (Penerbit UPSI, 2021)
This study aims to investigate if there a significant different in pre and post of Early Mathematics performance. A single group pre-test and post-test with intervening Early Mathematics based games was used in this research. This involved assessment on the early Mathematics abilities (Ginsburg & Baroody, 2003). This program was conducted among preschoolers (aged 5-6 years old) in one selected rural preschool in Menggatal district, Sabah. The school has 4 classes of 25 students each, with a total of 100 preschoolers. One sample t-test was conducted to compare mathematics ability of children before and after intervention. Mean score for pre-test is 15, while mean score for post-test is 22.32. There was a significant difference in the scores for mathematic ability in pre- test (M=15.78, SD=.99) and post-test (M=22.32, SD=.78), t (86) (=-28.52, p = 0.000). The results show that the use of games developed by authors are effective in improving preschoolers early Mathematics performance